Utilization From Waste Corn Silk (Zea Mays l.), Papaya Seeds (Carica Papaya l.), And Dragon Fruit Peels (Hylocereus Polyrhizus l.) For Health Herbal Tea - Ririn Riyani; Atha Adiwidya Ludfi; Royan Sevatama; Nurmala Fadhilah Djabbare; Satrio Trisulo Muwaffaq Dzulfiqar (Departement of Mathematics Education, 2024)
Tea can not only come from tea plants, but tea can come from a variety of ingredients such as spices, medicinal plants, and even waste from plants can be made into tea. An example is healthy herbal tea from corn silk, papaya seeds, and dragon fruit peels. The making of this herbal tea goes through the process of preparing the ingredients, separating the ingredients from the waste, washing the ingredients, draining the ingredients, cutting the dragon fruit peels, roasting the papaya seeds, drying the ingredients, crushing the ingredients, packaging the ingredients, and making herbal tea. In this study, 3 repetitions were carried out to achieve the right composition. After conducting 3 repetitions, based on the hedonic test, the most popular tea is Formula 3 with the composition of Corn Silk 40%, Papaya Seeds 20%, and Dragon Fruit Peels 40% and the percentage value for fragrance 83.33%, color 85.33%, and taste 82.00%. This herbal tea also passed tests such as phytochemical test, organoleptic test, pH test, and hedonic test. The conclusion of this study proves that all samples that have been tested react with reagents and prove that the preparation of tea bags contains alkaloid, flavonoid, steroid, saponin, and polyphenol compounds.